The systemic impact of a surgical procedure in older oncological patients. Issue 8 (August 2019) - Plas, Matthijs; de Haan, Jacco J.; van der Wal-Huisman, Hanneke; Rutgers, Abraham; Absalom, Anthony R.; de Bock, Geertruida H.; van Leeuwen, Barbara L.
Abstract: Background: An excessive inflammatory response accounts partially for the increased morbidity and mortality seen in elderly surgical patients. The aim of this study was to investigate the association between a range of pre- and peroperative factors and the extent of the inflammatory response, and to identify patients at risk of a greater inflammatory response following surgery. Methods: Patients 65 years and older undergoing a surgical procedure for a solid malignant tumour were prospectively included in an observational cohort study. Inflammatory markers were measured in plasma samples pre- and postoperatively: C-reactive protein (CRP), Interleukin-1 beta (IL-1β), IL-6, IL-10, IL-12, and Tumour necrosis factor alpha (TNF-α). Preoperative and postoperative inflammatory factor assay results were compared, and associations between inflammatory markers and pre- and peroperative factors were explored using multivariate linear regression analysis. Results: Between July 2010 and April 2014, plasma samples of 224 patients were obtained. Median age was 72 (65–89) years and 108 (48.2%) patients were male. The predominant diagnosis was carcinoma, 156 (69.6%). Anaesthesia duration was associated with increase in CRP, IL-1β and IL-6; intracavitary surgery with increase in IL-6; blood loss with decrease in CRP and IL-1β; total fluid volume administered with a decrease in IL-1β and disease stage was associated with increase in IL-6. Conclusions: The perioperative inflammatory response is related more to surgical characteristics rather than to preoperative factors (with the exception of disease stage). Elderly oncological patients undergoing longer lasting, intracavitary surgical procedures for more advanced disease stages develop the most intense inflammatory response.